Factores personales que influyen en el comportamiento de compra de calzado en los consumidores de la ciudad de Latacunga. - Guayaquil Madril, Tatiana Marisol (2018)
The objective of the research is to identify the factors that influence the purchasing behavior of footwear in the Latacunga city, which is why, according to the data provided by the IRS (Internal Rents Service) and the municipal GAD patent register of the Latacunga city, the sale of this product presents a problem regarding the decrease in sales and closing of commercial establishments in 2016 with 295 stores with an average annual sales of $ 1'680,844 and for the year 2017 with 256 stores with an average annual sales of $ 1476,306. The methodology I use is descriptive research, which uses methods for the field and bibliographic, facilitates the use of the tool for the collection of information in the PEA for a total of 63842 people. From the Latacunga city, of which a sample of 382 people was taken, comprised between men and women, from 18 to 61 years of age. With the corresponding tabulation, the analysis and interpretation of the data it was possible to reach the objective of the investigation, where the final report was determined that within the personal factors that make up the age and the life cycle of each individual the determining factor is the marital status, followed by the social environment, age, gender and family environment; Within occupation and economic circumstances the determining factor is the frequency of purchase, followed by the type of footwear and the average purchase; Within the lifestyle, the determining factor is that consumers feel more identified, followed by the color of preference, the factor on which it is based for the purchase decision and the place where the purchase is made more frequently; finally, the personality and the concept of the same where the determining factor is the means of communication followed by the motivation of the purchase.